The World and Vietnamese Economy in 2017, Prospects for 2018 and Some Policy Implications for Vietnam - Nhung, Nguyen Cam; Huong, Vu Thanh; Phuong, Nguyen Thi Minh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 1, 2018)
This paper assesses the comprehensive macroeconomic picture of the world and Vietnam in 2017 and forecasts the outlook for 2018, and then making some policy implications for Vietnam. The world economy in 2017 is considered to be the most prosperous since 2011, thanks to the steady growth of key economies, bounced global trade, and favorable global financial conditions. However, as slow and uncertain global investment growth as well as many unpredictable factors in US government policy and Brexit, and political risks from tensions of the Korean Peninsula, 2018 will continue to witness unpredictable developments in the global economy. Faced with that situation, together with internal difficulties in the country, Vietnam should have flexible solutions, high determination and act in a drastic way in order to achieve the objectives on the economic growth and inflation as outlined. In addition, Vietnam should continue to promote the trade facilitation activities, the improvement of the business investment environment, take advantage of new opportunities to attract foreign investment capital for infrastructure construction, keep on innovating, and enhance the competitiveness to bring our economy to the path of rapid and sustainable development.